Morphology of intermetallic phases in Al-Si cast alloys and their fracture behaviour - Lenka Hurtalová; Eva Tillová; Mária Chalupová; Juraj Belan (Production Engineering Archives, 2015)
Applications of Al-Si cast alloys in recent years have increased especially in the automotive industry (dynamic exposed cast, en-gine parts, cylinder heads, pistons and so on). Controlling the microstructure of secondary aluminium cast alloys is very important, because these alloys contain more additional elements that form various intermetallic phases in the structure. Therefore, the contribution is dealing with the valuation type of intermetallic phases and their identification with using optical and scanning microscopy. Some of the intermetallic phases could be identified on the basis of morphology but some of them must be identified according EDX analysis. The properties of alu-minium alloy are affected by morphology of intermetallic phases and therefore it is necessary to study morphology and its fracture behav-iour. The present work shows morphology and typical fracture behaviour as the most common intermetallic phases forming in Al-Si alloys.